A synthetic BBB-permeable tripeptide GCF confers neuroprotection by increasing glycine in the ischemic brain - Chen, Juan; Zhuang, Yang; Zhang, Ya; Liao, Huabao; Liu, Rui; Cheng, Jing; Zhang, Zhifeng; Sun, Jiangdong; Gao, Jingchen; Wang, Xiyuran; Chen, Shujun; Zhang, Liang; et al. (Frontiers in Pharmacology, 2022)
Background: We and others previously demonstrate that glycine is neuroprotective in cerebral ischemia-reperfusion injury. But glycine has low permeability to blood-brain barrier (BBB). To deliver glycine into the ischemic brain to confer neuroprotection, we designed a novel glycine-containing and BBB-permeable tripeptide, the H-glycine-cysteine-phenylalanine-OH (GCF). Methods: For the synthesis of GCF, phenylalanine was included to increase BBB permeability of the tripeptide. Cysteine was conjugated with glycine to enable the release of glycine from GCF. With the use of immunofluorescence labeling and HPLC assays, we measured the distribution and level of GCF. We used TTC labeling, LDH release and MTT assays to evaluate the neuroprotective effect of GCF. Results: Following intravenous injection in a rat model of cerebral ischemia-reperfusion injury, GCF was intensively distributed in the ischemic neurons. Intravenous injection of GCF, but not the non-cleavable acetyl-GCF, resulted in elevation of glycine in the ischemic brain. GCF but not acetyl-GC conferred neuroprotection in ischemic stroke animals. Conclusion: GCF protects against cerebral ischemia-reperfusion injury in rat. In contrast to peptide drugs that exert therapeutic effect by interfering signaling interaction, GCF acts as a BBB shuttle and prodrug to deliver glycine to confer neuroprotection, representing a novel therapeutic strategy for acute ischemic stroke.